The Role of Immunohistochemistry in the Workup of Malignant Neoplasms of Unknown Primary Origin at Khartoum Oncology Hospital - O.R Omar, Eiman; Emalaika Husain, Nazik; Ismail, Amal (Asian Pacific Journal of Cancer Care, 2021)
Background: Carcinoma of unknown primary origin (CUP) comprises various malignancies classified by detection of tissue-specific genes through immunohistochemistry (IHC). We aimed to explore the role of available immunohistochemical markers in diagnosing and classifying malignant neoplasms of unknown primary origin. Methods: A cross-sectional study included 141 patients diagnosed histologically as CUP and referred to the Histopathology and Immunohistochemistry Department, Khartoum Oncology Hospital, from 2012 to 2017. Hematoxylin and Eosin (H&E) and immune stained slides used in the workup were reviewed and classified into the main histologic types of CUP. Data were -analyzed by SPSS. Results: Out of 4436 cases, CUP represents (3.2%). The age group (60-69) years have the highest percentage (20.13%), with male predominance (51.77%). Lymph nodes represent (41.84%) followed by the liver (12.77%), spine (3.55%), and lungs (2.13%). Adenocarcinoma (75.89%) was the most common subtype, followed by undifferentiated neoplasm (14.18%), squamous cell carcinoma (7.09%), and carcinoma with neuroendocrine differentiation (2.84%). In 70 cases (49.6%) of the study cases, the primary site was determined, (17.7%) were given an only differential diagnosis, and in (32.6%) the origin remains unknown. Conclusions: CUP cases during the study period are infrequent (3.2%), and the primary origin was determined in nearly half of patients by the available immune markers. CUP’s common histological types were adenocarcinoma, undifferentiated neoplasm, squamous cell carcinoma, and carcinoma with neuroendocrine differentiation. The most common presenting sites were lymph node, liver, spine, and lungs.